PFM.24 Ultrasound assessment of chorionicity of twin pregnancies- how accurate are we?. (9th June 2014) - Doherty, E; Forrest, J; Fullerton, G; Bhattacharya, S
Abstract : Background: Chorionicity of twin pregnancies are important to determine for their clinical management. Routine ultrasound examination can determine this, but the accuracy and reliability of ultrasound is uncertain. Objectives: To determine the accuracy of antenatal ultrasound versus naked eye examination as a predictor of chorionicity of twin pregnancies in our unit. Methods: All twin deliveries occurring in 2007 to 2008 at the Aberdeen Maternity Hospital were identified from the Aberdeen Maternity and Neonatal Databank (AMND). Case notes were retrieved and ultrasound diagnosis of chorionicity and gestational age at examination were noted. The AMND recorded results of postnatal pathological examination of the placenta to determine chorionicity. Both methods of chorionicity assessment were compared using Kappa statistic. The sensitivity and specificity of each method were also assessed using the genetic determination of zygosity as the gold standard. Results: There were 150 twin deliveries in the study period after excluding those cases with missing chorionicity by either method. The proportion of agreement in monochorionic twins was 87% and that in dichorionic twins 99%. This gave a Kappa statistic of 0.89 indicating high agreement between the two methods. There were two discordant pairs and the ultrasound diagnosis was accurate in one of these as confirmed by assessment of zygosity. The false positive/negative cases were not associated with a later gestational age at ultrasound diagnosis. Conclusion: Antenatal determination of chorionicity by ultrasound is highly accurate and useful for informing clinical management of twin pregnancies.